Synthesis, Leishmanicidal and Cytotoxic Activity of Triclosan-Chalcone, Triclosan-Chromone and Triclosan-Coumarin Hybrids (2014)
ABSTRACT: Twelve hybrids derived from triclosan were obtained via Williamson etherification of O-triclosan alkyl bromide plus chalcone and O-coumarin or O-chromone alkyl bromide plus triclosan, respectively. Structures of the products were elucidated by spectroscopic analysis. The synthesized compounds were evaluated for antileishmanial activity against L. (V) panamensis amastigotes. Cytotoxic activity was also evaluated against mammalian U-937 cells. Compounds 7–9 and 17, were active against Leishmania parasites (EC50 = 9.4; 10.2; 13.5 and 27.5 µg/mL, respectively) and showed no toxicity toward mammalian cells (>200 µg/mL). They are potential candidates for antileishmanial drug development. Compounds 25–27, were active and cytotoxic. Further studies using other cell types are needed in order to discriminate whether the toxicity shown by these compounds is against tumor or non-tumor cells. The results indicate that compounds containing small alkyl chains show better selectivity indices. Moreover, Michael acceptor moieties may modify both the leishmanicidal activity and cytotoxicity. Further studies are required to evaluate if the in vitro activity against Leishmania panamensis demonstrated here is also observed in vivo.